Tingkat keterampilan pukulan Forehand Groundstroke tenis lapangan Mahasiswa FIK UNM - M. Sahib Saleh (Seminar Nasional LP2M UNM, 2019)
This study aims to find out empirically the level of forehand groundstroke skills in field tennis students at UNM FIK. The design of this study is a descriptive study. The population of this study were all students of FIK UNM and a sample of 28 male students. The method in this study uses survey methods and data collection techniques using tests and measurements. The instrument in this study used the Dyer tennis test that was relevant. With instrument validity between 0.85 and instrument reliability is 0.90. The data analysis technique of this study uses quantitative descriptive statistical analysis as outlined in the form of a percentage. The results of this study indicate that; detailed forehand groundstroke skill level of FIK UNM students from all 28 FIK UNM students, as follows: 3 students (10.7%) very low category; 4 students (14.3%) are in the low category; 11 students (39.3%) were in the medium category; 9 students (32.1%) were in the high category; and 1 student (3.6%) is in the very high category. Thus it can be concluded that the forehand groundstroke skill level is in the medium category